Regionalism, globalisation and international order : Europe and Southeast Asia - Wunderlich, Jens-Uwe, 1971- (Aldershot, England ; Burlington, VT : Ashgate, 2007)
"This study offers: an overview of new avenues in theorising regionalism; a consolidated framework for analysis and comparison; a comparative historical perspective of European and Southeast Asian regionalism; and new insights into the theory and practice of regionalism and the linkages between regional developments, globalisation, and international order."--Jacket.
Regionalism and integration theory the first wave: traditional approaches -- New regionalism: the second wave: towards a framework for comparative regionalism -- Regionalism in the EU and ASEAN during the Cold War: the first wave -- Second-wave regionalism: the Post-Cold War period -- Identifying regions: emerging regional identities in Europe and East Asia.
Includes bibliographical references (pages 171-199) and index.
Includes bibliographical references and index.
Keywords: ASEAN; European Union; 1950-2000; 2000-2010; Regionalism (International organization); International agencies -- Southeast Asia; Globalization; European Union; Economic integration